VIABILITAS DAN VIGOR BENIH CEMPEDAK ( Artocarpus champeden L.) PADA BERBAGAI MEDIA SIMPAN DENGAN LAMA PENYIMPANAN BERBEDA - Mukhsin Mukhsin; Neliyati Neliyati; Gusti Nopita (Fakultas Pertanian, Universitas Janabadra, 2024)
Cempedak seeds are recalcitrant seeds with high water content and are susceptible to a decrease in water content. Seed viability quickly decreases and eventually dies. Decreasing the water content below the critical point is a problem, high water content seeds germinate, and die if stored at low temperatures. With the right storage media, it is hoped that seeds can be stored longer so that seed viability and vigor can be maintained. This research aims to obtain appropriate storage media with a certain storage time that can maintain the viability and vigor of cempedak seeds. The research used a Completely Randomized Design (CRD) arranged factorially with two factors. The first factor of storage media (m) consists of m1: sawdust, m2: rice husks, and m3: coconut fiber powder. Meanwhile, the second factor is storage time (w) which consists of three treatment levels, namely w1: storage for 2 weeks, w2: storage for 4 weeks and w3: storage for 6 weeks. There were 9 treatments. Each treatment was repeated three times so that there were 27 experimental units. Each experimental unit contained 25 cempedak seeds. The variables observed were: seed water content, germination percentage, germination speed, germination uniformity and seedling dry weight. Data were analyzed using the F test and continued with the Duncan test at the α level of 5%. The results of the research showed that cempedak seeds stored in sawdust media for 4 weeks were able to maintain a water content of 36.24%, germination capacity of 69.33%, germination speed of 1.87%, germination simultaneity of 62.66% and seed dry weight. 8.37 grams.Key words: viability ; vigor ; storage media ; storage time; cempedak seeds